Correction method for mark positions in electronic book and computing device - ZOU JINBO; HUANG XINXIA (2018)
The invention discloses a correction method for mark positions in an electronic book and a computing device. The method comprises the steps that for any mark in the electronic book, an initial position deviation value of the mark is acquired, and an initial character deviation value of at least one specific word is acquired; according to the initial position deviation value of the mark and the initial character deviation value of the at least one specific word, whether one or more specific words with initial character positions previous to the initial position of the mark exist is judged through search; and if yes, according to the difference between the quantity of characters of the one or more specific words and the quantity of characters of corresponding replacement words, the positionof the mark is corrected. Through the method, a scheme for performing unified correction processing on the mark positions is provided, the mark positions are corrected according to the difference between the quantity of the c